Laser-puncture Versus Electrosurgery-incision of the Ureterocele in Neonatal Patients - Ilic, Predrag; Jankovic, Mirjana; Milickovic, Maja; Dzambasanovic, Slobodan; Kojovic, Vladimir (Urology Journal, 2018)
Purpose: To compare the holmium-laser puncture and electrosurgery-incision in neonates with intravesical ureterocele. Materials and Methods: We retrospectively analyzed the results of laser-puncture of ureterocele (LP group) in 12 patients (mean age 9.8 days, range 4-28) and electrosurgery-incision in 20 patients (ES group) (mean age 10.2 days, range 6-28), treated at our institution. Patients had their records reviewed for preoperative findings, endoscopic procedure description, and postoperative outcomes. Results: There was the need for retreatment in one (8.3%) patient in LP group and in four (20%) patients in ES group (P = .626). Duration of general anesthesia in LP and ES groups was 16 (range, 10-24) minutes and 15 (range, 10-20) minutes, respectively (P = .355). There was no statistically significant difference in terms of hospitalization (LF group one day, ES group 1.35 days) (P = .286). Complications were not found in LP group. There were two (10%) patients with pyelonephritis after the treatment in ES group (P = .516). After one month, obstruction was observed on ultarsound examination in one (8.3%) and two (10%) patients, respectively. After three months, obstruction was not found in any patient in both groups. After six months, vesicoureteral reflux was found in one (8.3%) patient after laser-puncture of the ureterocele and in 13 (65%) patients after electrosurgery-incision (P = .003). Conclusion: Both laser-puncture and electrosurgery-incision endoscopic techniques are highly effective in relieving the obstruction. There is no significant difference regarding hospitalization, need for retreatment and the occurrence of complications. The incidence of de novo vesicoureteral reflux is significantly lower in patients treated with holmium-laser, as well as the need for upper pole partial nephrectomy.